Solution structure of a hexitol nucleic acid duplex with four consecutive T center dot T base pairs - Lescrinier, E; Esnouf, R; Schraml, J; Busson, R; Herdewijn, P (2000)
The structure of the hexitol nucleic acid (HNA) h(GCGCTTTTGCGC) was determined by NMR spectroscopy. This unnatural nucleic acid was developed as a mimic for A-RNA. In solution, the studied sequence is forming a symmetric double-stranded structure with four central consecutive T·T wobble pairs flanked by G·C Watson-Crick base pairs. The stem regions adopt an A-type helical structure. Discrete changes in backbone angles are altering the course of the helix axis in the internal loop region. Two H-bonds are formed in each wobble pair, and base stacking is preserved in the duplex, explaining the stability of the duplex. This structure elucidation provides information about the influence of a (T)4 fragment on local helix geometries as well as on the nature of the T·T mismatch base pairing in a TTTT tract.